Analysis of the NK2 homeobox gene ceh-24 reveals sublateral motor neuron control of left-right turning during sleep - Juliane Schwarz; Henrik Bringmann (eLife, 2017)
Sleep is a behavior that is found in all animals that have a nervous system and that have been studied carefully. In Caenorhabditis elegans larvae, sleep is associated with a turning behavior, called flipping, in which animals rotate 180° about their longitudinal axis. However, the molecular and neural substrates of this enigmatic behavior are not known. Here, we identified the conserved NK-2 homeobox gene ceh-24 to be crucially required for flipping. ceh-24 is required for the formation of processes and for cholinergic function of sublateral motor neurons, which separately innervate the four body muscle quadrants. Knockdown of cholinergic function in a subset of these sublateral neurons, the SIAs, abolishes flipping. The SIAs depolarize during flipping and their optogenetic activation induces flipping in a fraction of events. Thus, we identified the sublateral SIA neurons to control the three-dimensional movements of flipping. These neurons may also control other types of motion.